Multiple pathophysiological biomarkers are associated with gray matter volume and cerebral glucose metabolism in the early preclinical Alzheimer's continuum: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Gispert, Juan Domingo; Salvadó, Gemma; Milà‐Alomà, Marta; Cacciaglia, Raffaele; Falcon, Carles; Operto, Greg; Grau‐Rivera, Oriol; Arenaza‐Urquijo, Eider M; Shekari, Mahnaz; Minguillón, Carolina; Fauria, Karine; Kollmorgen, Gwendlyn; et al.
Abstract: Background: The pathophysiological events that occur early in the preclinical Alzheimer's disease (AD) continuum are not fully understood. Here, we sought for associations, in cognitively unimpaired individuals, between cerebrospinal (CSF) biomarkers of the main pathophysiological events described in AD vs. patterns of gray matter volume (GMv) and cerebral glucose metabolism (rCMRGlu). Method: The first consecutive 381 participants of the ALFA+ study with valid T1w MRI, [ 18 F]FDG‐PET scans and CSF samples were included. CSF biomarkers were measured with the NeuroToolKit robust prototype assays and Elecsys® immunoassays (Roche Diagnostics) and related to amyloid (Aβ42, Aβ40) and tau (pTau) metabolism, neuronal and axonal damage (NfL), synaptic dysfunction (neurogranin), neuroinflammation (sTREM2, YKL40, GFAP, S100, IL6), and α‐synuclein. Individuals were staged using the A/T system and pre‐established cut‐offs for the Aβ42/40 ratio and pTau concentrations. Modulated GMv maps were obtained from T1w scans. [ 18 F]FDG uptake was normalized to the pons. Exploratory voxelwise associations between maps of GMv and rCMRGlu vs. CSF biomarkers (and differences between A/T groups in the AD continuum ) were assessed with SPM12 (p<0.005, k>50 voxels) after accounting for the effect of age, sex, education, and APOE ‐ε4 carriership, as well as for the Total Intracranial Volume (TIV) in the GMv analysis. Result: Demographics are shown in Table 1. Figure 1 shows regional differences in GMv and rCMRGlu between A/T groups and Figure 2 associations with biomarkers. Compared to the A‐T‐ group, A+T‐ individuals presented a widespread pattern of higher GMv. Higher pTau levels were associated with an extensive pattern of higher GMv and rCMRGlu. Higher sTREM2 values were associated with higher GMv in the temporoparietal junction and posterior cingulate cortex overlapping pTau GMv effects (Figure 3). Lower Aβ42/40 values were also associated to lower rCMRGlu in bilateral hippocampus and anterior cingulate. Higher NfL levels were coupled with lower GMv in bilateral parietotemporal cortices. Conclusion: Results suggest that pathogenic events in very early stages of the Alzheimer's continuum are unexpectedly associated with higher GMv and rCMRGlu. The overlap of pTau and sTREM2 effects in GMv may point towards a TREM2‐mediated microglial reaction to initial tau pathology. Interactions between biomarkers and A/T groups will be presented.